Application of Pop Up Book Media to Optimize Science Learning Outcomes - Amalia, Aniq Setia; Setiyawati, Dewi (UIN Fatmawati Sukarno Bengkulu, 2020)
Science Learning in MI Ma'arif Kumpulrejo 02 Salatiga has not used a variety of active and creative learning media. This causes students to be passive and the lack of student attention to the material delivered by the teacher. Evidenced by the low learning outcomes of students who have not yet reached the KKM determined by the school 65. The purpose of this study was to determine the increase in science learning outcomes through Pop-Up book media in class IV MI Ma'arif Kumpulrejo 02 Salatiga. This research is a classroom action research conducted in three cycles, namely Cycle I, Cycle II, and Cycle III. Each cycle consists of four stages, namely planning, implementing, observing, and reflecting. The subjects of this study were class IV students, totaling 28 students. Data collection methods are interviews, observation, and documentation. The results of the study stated that the results of the first cycle of completeness student learning outcomes amounted to 39.29% (11 students completed KKM). These results have not yet reached the indicator of success, which is ≥85% so that it is continued in the second cycle. Cycle II completeness of student learning by 64.29% (18 students completed KKM) so that from cycle I to cycle II increased learning outcomes by 25%. However, in cycle II it still does not meet the indicators of success so it needs to be continued on cycle III. Cycle III completeness of student learning by 85.71% (24 students completed KKM). In this third cycle student learning outcomes have met the indicator of learning success that is 85%. Thus, it can be concluded that the application of Pop-Up book media can improve the learning outcomes of science in class IV MI Ma'arif Kumpulrejo 02 Salatiga.